Analysis Of BPJS Types, Access And Aspects Interpersonal On Satisfaction Patients At The Health Center Medokan Ayu Surabaya - Putu Surabela Paramita; Riza Yuliawati (Universitas STRADA Indonesia, 2024)
Patient satisfaction is one of the goals of the Surabaya City Government in the 2016 - 2021 RPJMD which has been formulated in the performance of government administration and public services with the target of increasing the capacity and competence of government officials, improving good government administration and improving the quality of public services. This type of research is cross sectional study. Analytical survey research design. The population is BPJS patients at the Medokan Ayu Surabaya Community Health Center in 2021, totaling 310 respondents in the last 3 months. The sampling technique used accidental sampling so that the sample was 75 people. Data collection uses questionnaires, and data analysis uses contingency coefficient correlation. The results of the research show that bivariate analysis with the results of the correlation hypothesis test of the contingency coefficient for each variable, obtained a BPJS type variable with a p-value of 0.002 (p<0.005) with a correlation coefficient value of 0.346, meaning that the level of strength of the relationship is sufficient and the value is positive so that the relationship is in the same direction. The access variable has a p-value of 0.000 (p<0.005) with a correlation coefficient of 0.429, meaning that the level of strength of the relationship is sufficient and the value is positive so that the relationship is in the same direction. The interpersonal aspect variable has a p-value of 0.001 (p<0.005) with a correlation coefficient of 0.402, meaning that the level of relationship strength is sufficient and the value is positive so that the relationship is in the same direction. Patient satisfaction is an important element in evaluating the quality of BPJS services by measuring the patient's response after receiving the service. With an assessment of these services, it is hoped that these health service facilities will continue to exist and continue to develop (Abidin, 2016). Several factors that give rise to a sense of satisfaction in patients are access, interpersonal aspects. Based on this, the researchers assume there is a relationship between BPJS Type, Access and Interpersonal Aspects on patient satisfaction at the Medokan Ayu Surabaya Community Health Center in 2021.